PENGARUH LOKASI, PERSEPSI HARGA DAN DAYA TARIK WISATA TERHADAP KEPUTUSAN BERKUNJUNG DI WISATA PANTAI LAPADE - Arsita, Asri; Hartini (Jurnal Nusa Manajemen, 2024)
This study aims to examine the Influence of Location, Price Perception and Tourism Attractiveness on the Decision to Visit Lapade Beach Tourism. Lapade Beach is a beach located in the sub-district of Utan providing a variety of games. This study used quantitative methods with an associative approach. The data collection method in this study used a questionnaire with a Likert scale. The sampling method uses purposive sampling and the sample used by 100 respondents. In this study, the datawas processed using the SPSS 23 application and data analysis was carried out with multiple linsear regression analysis techniques. The results of this study show that location has a significant effect on visiting decisions, price perception has asignificant effect on visiting decisions, Tourism Attraction has a significant effect on Visiting Decisions at Lapade Beach Tourism.